The impact of walkable environment on single-family residential property values - Yuntao Guo; Srinivas Peeta; Sekhar Somenahalli (Journal of Transport and Land Use)
Due to the impact of urban sprawl, the need for responsible property investing, and the emerging evidence supporting the linkage between walkable environment (in terms of built environment and walk accessibility) and residential property value, there is a critical need to develop systematic methodologies to quantify the impact of walkable environment on residential property value. This study provides a new generalized dissimilarity index for quantifying land-use mix, a key component of built environment, and a new method for measuring a property’s walk accessibility and then links them to residential property values. Ordinary least squares (OLS) regression models are used to validate these methods by examining the empirical property data in Eastern Adelaide, Australia. The results of the OLS models show that the proposed dissimilarity index and property walk-accessibility method outperform other commonly used land-use mix quantification and walk-accessibility methods in estimating single-family residential property values in terms of the goodness-of-fit and explanatory power. This study provides insights for investors to understand the impact of walkable environment on single-family residential property values to enable them to make more informed decisions on property investment, and for planners to design neighborhoods featuring better walkable environments.